DAMPAK KETERGANTUNGAN GADGET TERHADAP GANGGUAN EMOSI DAN KESEHATAN FISIK SISWA/SISWI SMP NEGERI 85 JAKARTA SELATAN - Azhar Alkautsar (2021)
The high usage of smartphones these days may have positive or adverse effects. The negative impact of smartphone addiction can include physical health problems and emotional disorders in children/adolescents. Therefore, further research is needed about the relationship between smartphone addiction to physical health and emotional disorders in adolescents. This study's objective was to determine the relationship between smartphone addiction to physical health and emotional disorders in SMPN 85 South Jakarta students. This study's sample was students of SMPN 85 South Jakarta who was included in the inclusion and exclusion criteria. Observational analysis with a cross-sectional approach was used in this study. The Short Version Smartphone Addiction Scale questionnaire, WHOQOL-BREF, and the Strength Difficulty Questionnaire have been validated. A sampling of 90 respondents was carried out by random sampling method. This study proves a significant relationship (p = 0.013) between smartphone addiction and emotional disorders in students of SMPN 85 South Jakarta and proves that there is no significant relationship (p = 0.883) between smartphone addiction and physical health